Designing, launching, and implementing high quality learning opportunities for students that advance scientific thinking. Issue 9 (6th May 2016) - Kang, Hosun; Windschitl, Mark; Stroupe, David; Thompson, Jessica
Abstract: Instructional tasks are key features of classroom practice, but little is known about how different components of tasks—such as selecting or designing tasks for a lesson, launching, and implementing them with students—shape the conditions for students' intellectual engagement in science classrooms. Employing a qualitative multiple case study approach, we analyzed 57 science lessons taught by 19 first‐year teachers. We examined the potential for students' intellectual work built into the tasks across the phases of instruction, and how the demand of the unfolding task deepened (or failed to deepen) students' engagement in science. The findings suggest the importance of beginning a lesson with high quality instructional tasks—complex tasks that bear appropriate levels of epistemic uncertainty for a particular group of students in a particular moment. Beginning a lesson with high quality tasks; however, was insufficient by itself to ensure rigorous learning opportunities. With the use of complex tasks, higher quality opportunities to learn were observed in lessons in which: (i) the tasks were framed as a process of understanding contextualized phenomena; (ii) the specific disciplinary concepts in the task were related to big science ideas that transcended the activities themselves; and (iii) students' implementation of these tasks were structured using tools that supported changes in thinking. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1316–1340, 2016